Theoretical foundations of the «project» («international project») concepts study and the impact of project management on the development of business enterprises - A.S. Polianska (Економіка, управління та адміністрування)
The article considers approaches to the interpretation of the concepts «project» and «international project», defines typical classifications of projects, gives several features and elements of the project, and defines the main stages of international project implementation. An analysis of the «project management / international project» concept is made, the implementation of which affects the socio-economic indicators of the country’s development as a whole and is an important factor in improving both national and international business activities of enterprises. Project management is becoming more important in both the public and private sectors of the economy because it develops the ability to plan, and organize the work process, and forms the ability to direct resources and exercise control over them to achieve specific goals. International projects are gradually becoming more important, attracting partners from different countries and contributing to the development and expansion of foreign economic ties.